HMGB1 Promotes Systemic Lupus Erythematosus by Enhancing Macrophage Inflammatory Response - Mudan Lu; Shanshan Yu; Wei Xu; Bo Gao; Sidong Xiong (Journal of Immunology Research)
Background/Purpose. HMGB1, which may act as a proinflammatory mediator, has been proposed to contribute to the pathogenesis of multiple chronic inflammatory and autoimmune diseases including systemic lupus erythematosus (SLE); however, the precise mechanism of HMGB1 in the pathogenic process of SLE remains obscure. Method. The expression of HMGB1 was measured by ELISA and western blot. The ELISA was also applied to detect proinflammatory cytokines levels. Furthermore, nephritic pathology was evaluated by H&E staining of renal tissues. Results. In this study, we found that HMGB1 levels were significantly increased and correlated with SLE disease activity in both clinical patients and murine model. Furthermore, gain- and loss-of-function analysis showed that HMGB1 exacerbated the severity of SLE. Of note, the HMGB1 levels were found to be associated with the levels of proinflammatory cytokines such as TNF-α and IL-6 in SLE patients. Further study demonstrated that increased HMGB1 expression deteriorated the severity of SLE via enhancing macrophage inflammatory response. Moreover, we found that receptor of advanced glycation end products played a critical role in HMGB1-mediated macrophage inflammatory response. Conclusion. These findings suggested that HMGB1 might be a risk factor for SLE, and manipulation of HMGB1 signaling might provide a therapeutic strategy for SLE.